The Utilization of Solar Cell for Power Lighting Equipment on the Ferry - Faturachman, Danny; Shariman, Mustafa; Muslim, Muswar (2013)
An electric motor become much more practical and economical having a multiplicity findings on the technology of solar panels, battery and charger better. An electric motor cost-effective care and in working. The installation of an electric motor more simple and does not need the cooler. All the needs of electrical power in supply from batteries being replenished by solar panels. Solar power become one of alternative energy to overcome the presence of the energy crisis especially a reduction in the availability of petroleum and the more expensive world oil prices. Major problems focused on design of electric system as power plant resources in the ship. The main issues discussed on is as follows: 1. Did design system supply resources and also calculation to determine battery and solar panels to be used. 2. Determine the laying on systems equipment. In this research, taking and analyzing data obtained from the results of the field by using the existing theory and make use of data from the internet and literature data. In duty end of this analysis conducted by the use of solar power as the supply of equipment lighting on a ship ferry Ro-Ro 500 GRT. Based on calculations data ship obtained a number of 35 solar panels that is attached to supply 10 batteries power by producing 42000 VA. Power is used to meet the needs of illumination burden 33600 VA to the discharging time 12 hours (from 18.00 – 6.00). So that the installation of solar systems can save energy by 52.5 % of the generator burden.